THE QUR'ANIC SEMANTIC LANDSCAPE OF ȘALĀH: EVOLUTION AND INTERPRETATION - Andi, Azhari (Mazalat: Jurnal Pemikiran Islam, 2024)
This article aims to examine the term șalāh in the Qur'an. While most Muslims understand șalāh as a ritual that begins with takbir and ends with salam, this perspective limits the comprehensive meaning of șalāh. The Qur'an, however, employs the term in various contexts and with multiple nuances. This study adopts the semantic framework of Toshihiko Izutsu to explore and analyze these different uses. The findings reveal that in the Qur'an, șalāh encompasses a range of meanings beyond obligatory prayers, including recitation of the Qur'an, supplication, mercy, blessings, and places of worship. The semantic evolution of șalāh spans from pre-Qur'anic times to the post-Qur'anic era. In the pre-Qur'anic period, șalāh generally referred to prayers with worldly connotations and expressions of respect for rulers. During the Qur'anic period, the meaning of șalāh shifted towards spiritual and eschatological dimensions. In the post-Qur'anic era, particularly within fiqh literature, the term has been narrowly interpreted as obligatory prayers and related ritual acts. This study highlights the dynamic nature of șalāh’s semantic development and its broader implications within Islamic thought.